Optimal active target localisation strategy with range-only measurements - He, Shaoming; Shin, Hyo-Sang; Tsourdos, Antonios (INSTICC, 2019)
This paper investigates the problem of one-step ahead optimal active sensing strategy to minimise estimation errors with range-only measurements for non-manoeuvring target. The determinant of Fisher Information Matrix (FIM) is utilized as the objective function in the proposed optimisation problem since it quantifies the volume of uncertainty ellipsoid of any efficient estimator. In consideration of physical velocity and turning rate constraints, the optimal heading angle command that maximises the cost function is derived analytically. Simulations are conducted to validate the analytical findings.
Keywords: Target localisation; Range-only measurement; Optimal manoeuvre